(untitled) (Revista Brasileira de Contabilidade e Gestão, 2020)
The objective is to study the perceptions of magistrates regarding changes in labor legislation and the role of accounting experts. To reach the goal, a field survey was conducted. The sample of the research, would be composed by all the Magistrates of the Circumscription of Brasília, but not all accepted. Thus, the final sample consisted of ten judges holding the 10 th Regional Labor Court. The paper presen ts the most significant changes in the magistrates’ view, and their position in relation to the changes are positive or negative. Based on Bardin’s Content Analysis (2011), the division was divided into thematic categories and it was concluded that there are numerous controversial points in the new law and some are considered by the magistrates as unconstitutional. For the accountants, the Labor Reform can bring two impacts: the first is a new possibility of work, because now there is the need for the requests to be settled from the beginning and thus the party will seek the services of the accountant already in the initial phase of the process; the second is that now the responsibility for the payment of expert fees becomes the succumbing party in the claim object of the expert, even if beneficiary of the free trial. This may be due to a lack of accounting experts.